Nauka języków obcych uczniów z dysfunkcją słuchu - Skowronek, Barbara (Scripta Neophilologica Posnaniensia, 2021)
Hearing impaired people have serious communication problems: both with (full) understanding of reality and with learning the first language. In order to counteract communication exclusion, they compensate for the deficiencies with an increased use of other senses. They learn the first language consciously with the help of a speech therapist, compensating for hearing dysfunctions, e.g. wide-angle vision. Karpińska-Szaj calls such learning inclusive; they can be successfully used in teaching foreign languages.